2014
DOI: 10.1016/j.celrep.2014.10.035
|View full text |Cite
|
Sign up to set email alerts
|

Independent Component Analysis Uncovers the Landscape of the Bladder Tumor Transcriptome and Reveals Insights into Luminal and Basal Subtypes

Abstract: Extracting relevant information from large-scale data offers unprecedented opportunities in cancerology. We applied independent component analysis (ICA) to bladder cancer transcriptome data sets and interpreted the components using gene enrichment analysis and tumor-associated molecular, clinicopathological, and processing information. We identified components associated with biological processes of tumor cells or the tumor microenvironment, and other components revealed technical biases. Applying ICA to nine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
229
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(248 citation statements)
references
References 35 publications
17
229
0
2
Order By: Relevance
“…In addition, a singlesample enrichment analysis for rank-normalized CERES gene effects across the mammalian protein complexes in the CORUM database (38) demonstrated that neuroblastoma is the cancer type most dependent on the EED/EZH2 complex compared with all other cancer types screened ( Figure 1C and Supplemental Figure 1A). The EZH2, SUZ12, and EED dependency scores demonstrate individual dependency across subused for the analysis of biological data that involve higherorder associations, such as identifying tumor-related pathways in transcriptional data sets, classifying disease lineages, characterizing transcriptional regulators, and identifying disease-specific biomarkers (31)(32)(33)(34)(35)(36)(37). Thus, we applied ICA to rank-normalized CRISPR-Cas9 screening data and identified the top 3 independent components (IC1, IC2, and IC3) that were significantly depleted in neuroblastoma compared with other cancer cell lines screened ( Figure 1A).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, a singlesample enrichment analysis for rank-normalized CERES gene effects across the mammalian protein complexes in the CORUM database (38) demonstrated that neuroblastoma is the cancer type most dependent on the EED/EZH2 complex compared with all other cancer types screened ( Figure 1C and Supplemental Figure 1A). The EZH2, SUZ12, and EED dependency scores demonstrate individual dependency across subused for the analysis of biological data that involve higherorder associations, such as identifying tumor-related pathways in transcriptional data sets, classifying disease lineages, characterizing transcriptional regulators, and identifying disease-specific biomarkers (31)(32)(33)(34)(35)(36)(37). Thus, we applied ICA to rank-normalized CRISPR-Cas9 screening data and identified the top 3 independent components (IC1, IC2, and IC3) that were significantly depleted in neuroblastoma compared with other cancer cell lines screened ( Figure 1A).…”
Section: Resultsmentioning
confidence: 99%
“…Genomic 'subtypes' and genetic alterations with distinct molecular profiles and varied response to NAC have been described [19][20][21][22][23] . As our understanding of MIBC biology continues to evolve, more 'personalized' treatment decisions will allow us to better select chemo sensitive tumors.…”
Section: Cuaj -Original Researchmentioning
confidence: 99%
“…Dyrskjøt et al (11) detected carcinoma in situ gene expression that is reflected in carcinoma in situ biopsies and superficial transitional cell carcinoma. Biton et al (12) demonstrated that a molecular urothelial differentiation program was maintained by applying independent component analysis to bladder cancer transcriptome data and exploiting additional molecular and clinic pathological data.…”
Section: Introductionmentioning
confidence: 99%